English Speaking Skill and Language Component Practice: englisch-hilfen.de in Assistance - Huda, Nurul; Hotimah, Husnul (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2020)
English Foreign Language (EFL) students, most of the time, face difficulties in learning English, especially in mastering speaking skills. One of the most common problems faced in the teaching and learning process for speaking skills is the lack of motivation and students tend to use their first language. As the development of technology, the teacher is required to involve digital teaching, especially related to the use of computers. Employing computer or Computer-Assisted Language Learning (CALL) in the teaching and learning process is highly recommended for a fun and exciting learning. In this particular case, englishch-hilfen.de serves as an answer for those seeking such a learning process. A qualitative study was involved to identify how the use of englishch-hilfen.de can improve and give a significant effect on students’ English performance, especially for speaking and vocabulary aspects. The result of this study suggested that the content within englishch-hilfen.de is very beneficial for it provides such meaningful and stimulating activities for English language students.